2010
DOI: 10.1071/an09085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave treatment on lucerne fodder

Abstract: Preliminary research has suggested that in vitro dry matter disappearance of some poor-quality fodder materials can be improved by microwave treatment. A laboratory-scale experiment that treated 50-g samples of lucerne hay in a 750-W microwave oven for 0, 40 and 80 s revealed that dry matter percentage increased by 1.7% as microwave treatment time increased from 0 to 80 s. The in vitro dry matter disappearance increased by 14.9% as microwave treatment increased from 0 to 80 s; however, there was no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Small scale in vitro pepsin-cellulase digestion experiments [103], similar to the technique developed by McLeod and Minson [104,105], demonstrated that microwave treatment: increased dry matter percentage with increasing microwave treatment time; increased in vitro dry matter disappearance with increasing microwave treatment time; but had no significant effect on post-digestion crude protein content.…”
Section: Microwave Treatment Of Animal Foddermentioning
confidence: 86%
See 3 more Smart Citations
“…Small scale in vitro pepsin-cellulase digestion experiments [103], similar to the technique developed by McLeod and Minson [104,105], demonstrated that microwave treatment: increased dry matter percentage with increasing microwave treatment time; increased in vitro dry matter disappearance with increasing microwave treatment time; but had no significant effect on post-digestion crude protein content.…”
Section: Microwave Treatment Of Animal Foddermentioning
confidence: 86%
“…The sudden jump in the heating rate after some time of steady heating may be evidence of thermal runaway ( Figure 9). Observation of the treated chaff showed no signs of charring; however the chaff was dry and crisp [103]. The onset of thermal runaway dramatically increases the heating efficiency.…”
Section: Microwave Treatment Of Animal Foddermentioning
confidence: 92%
See 2 more Smart Citations
“…Microwave energy has also been used to manage weeds and other soil born pathogens (Nelson, 1987;Bansal, 2006) and to treat various animal feeds to improve their digestibility (Sadeghi & Shawrang, 2006Brodie et al, 2010). Microwaves are commonly used to process ceramics (Takayama et al, 2005) and can be used to drill through ceramics and glass (Jerby et al, 2002).…”
Section: Applications Of Microwave Heatingmentioning
confidence: 99%